(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Comprehensive and inclusive spatial planning is important for the long-term, equitable provision of supportive environments that enable health-enhancing physical activity (HEPA), especially in public outdoor spaces and green areas that contribute to the public good. The success of these efforts relies heavily on understanding the needs, attitudes, values, and preferences of residents, as well as the effective coordination of policies and actions across sectors that influence both spatial and social conditions. Co-creation enhances this process by fostering inclusivity, enabling local communities and a diverse range of stakeholders to actively engage in urban planning and design. Project Description: The JPI Urban Europe project C3Places – Using ICT for Co-Creation of Inclusive Public Places (https://myc3place.di.unimi.it/; 2017–2020) focused on exploring the potential and challenges of stakeholder engagement and co-creation to enhance the quality of public open spaces. The project aimed to improve these spaces by fostering co-creation and social cohesion through the use of digital technologies. The evaluation of the suitability of digital tools was based on the Digital Co-Creation Index, which assesses and compares digital co-creation initiatives. The evaluation framework addressed three key aspects: spatial quality, focusing on accessibility, safety, and the variety of activities; user-related factors, including interactivity, usability, and user safety; and technological requirements, covering the functionality, installation, and accessibility of ICT tools. Living Labs in Belgium, Italy, Lithuania, and Portugal tested the impact of ICT tools across diverse user groups and urban spaces, guided by a unified methodological framework for structured evaluation. The project addressed key challenges and opportunities in involving various stakeholders across the sequential phases of public outdoor space development. These phases include identifying needs, problems, and opportunities; shaping initiatives, goals, and visions; developing and evaluating proposals and solutions; decision-making; implementation; and, finally, use and management. A methodological model was created, including a visual scheme that illustrates the interconnection and sequence of these stages. It highlights the necessary activities for each phase, the roles and responsibilities of involved actors, and the expected outcomes at each step of the process. Conclusion: Innovative co-creation model that is closely related to the spatial planning process helps to engage the public and various sectors in developing supportive environments for HEPA in a way that is beneficial for everyone. This model provides a strong foundation for involving the public and multiple sectors in the comprehensive and mutually beneficial development of supportive spatial and other conditions for HEPA. Keywords: Co-creation, public space improvement, stakeholder collaboration, ICT-enabled participation, health-enhancing physical activity (HEPA)